Algorithms and discrete applied mathematics : Second International Conference, CALDAM 2016 Thiruvananthapuram, India, February 18-20, 2016 Proceedings /: Second International Conference, CALDAM 2016 Thiruvananthapuram, India, February 18-20, 2016 Proceedings. (2016) - Unknown
No abstract available